Foreign investment in Southeast Asia in the twentieth century - Lindblad, J. Thomas (St. Martin's Press, 1998)
This monograph is the first book-length study of foreign direct investment in Southeast Asia during both the late colonial period and in the contemporary period. It examines the leading Southeast Asian countries receiving foreign investment this century. The arrival of today's Asian investors, from Japan and the four Asian NICs, is described after a brief discussion of the transitionary period of warfare, decolonization and assertion of newly independent states. Special attention is given to the impact of foreign investment on the economic development of the host country.